Beneficial Effect of Renal Denervation on Ventricular Premature Complex Induced Cardiomyopathy. Issue 3 (March 2017) - Yamada, Shinya; Lo, Li‐Wei; Chou, Yu‐Hui; Lin, Wei‐Lun; Chang, Shih‐Lin; Lin, Yenn‐Jiang; Liu, Shin‐Huei; Cheng, Wen‐Han; Tsai, Tsung‐Ying; Chen, Shih‐Ann
Abstract : Background: Frequent ventricular premature complexes (VPCs) can lead to the development of dilated cardiomyopathy and sudden cardiac death. Renal artery sympathetic denervation (RDN) may protect the heart from remodeling. This study aimed to investigate the effect of frequent VPCs on structural and electrical properties and whether RDN can protect the heart from remodeling. Methods and Results: Eighteen rabbits were randomized to control (n=6), VPC (n=6), and VPC‐RDN (n=6) groups. Surgical and chemical RDNs were approached through bilateral retroperitoneal flank incisions in the VPC‐RDN group. Pacemakers were implanted to the left ventricular apex to produce 50% VPC burden for 5 weeks in the VPC and VPC‐RDN groups. In addition, ventricular myocardium was harvested for western blot and trichrome stain. Echocardiographic results showed left ventricular enlargement after 5‐week pacing in the VPC group, but not in the VPC‐RDN group, when compared to baseline. In biventricles, ion channel protein expressions of Nav1.5, Cav1.2, Kir2.1, and SERCA2 were similar among 3 groups. However, the degree of biventricular fibrosis was extensive in the VPC group, compared to the control and VPC‐RDN groups. Importantly, ventricular fibrillation inducibility was higher in the VPC group (41%) when comparing to the control (13%; P <0.05) and VPC‐RDN groups (13%; P <0.05), respectively. Conclusions: Frequent VPCs are associated with the development of cardiac structural remodeling and high ventricular fibrillation inducibility. RDN prevents cardiac remodeling and the occurrence of ventricular arrhythmia through antifibrosis.